Oxidative stress markers in mild hypertension - Oré, Raquel (2007)
Introduction: Hypertension is a cardiovascular risk factor and the initial mechanism is unknown in 90% of the cases. Currently hypertension is considered a syndrome with metabolic and structural abnormalities where oxygen reactive species (ORS) play a preponderant pathophysiological role. Objective: To determine zinc, selenium and magnesium serum levels in hypertensive and normotensive subjects, and to measure superoxide dismutase (SOD) activity and thiobarbituric acid reactive substances (TBARS) levels in both groups. Design: Analytical observational, case-control study. Setting: Biochemistry and Nutrition Research Center, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological material: Normotensive and mild hypertensive patients blood samples. Interventions: Blood samples from 20 normotensive subjects and 20 patients with mild hypertension aged 50 to 60 years were obtained after 12-hour fasting. We studied serum and whole blood. Main outcome measures: Serum determination of TBARS and oligoelements (Zn and Mg), measurement of SOD erythrocytic activity. Results: In the hypertensive group we obtained significant increase in magnesium and TBARS, and significant decrease in zinc and SOD activity. Conclusions: We demonstrated the occurrence of oxidative stress in mild hypertensive patients. Hypermagnesemia could be explained by blood elements injury.